Pentingnya Disiplin dalam Peningkatan Kinerja Aparat Pemerintahan Kampung Wanggarsari Distrik Wangar Kabupaten Nabire: Kajian Berdasarkan UU Nomor 23 Tahun 2014 Tentang Pemerintahan Daerah dan UU Nomor 30 Tahun 2014 tentang Administrasi Pemerintahan - Petrus Tekege (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
This article is the result of a literature and empirical study adapted to developments in employee disciplinary law. The purpose of this writing is simply to provide an overview of information about the disciplinary laws of government agencies in carrying out their duties and responsibilities to improve performance in services to the community. This research uses a literature review and empirical study approach. Discipline of Wanggarsari village officials to improve performance in accordance with Law Number 9 of 2015 as a result of amendments to Law Number 23 of 2014 concerning regional government and Law No. 30 of 2014 concerning Government Administration has not been implemented optimally, because work is not disciplined, not in accordance with the accuracy of completing tasks and so on, so that performance improvements have not been achieved according to expectations, both community expectations and the expectations of the law. The performance of Wanggarsari village officials will improve if Wanggarsari village officials in Wanggar District are aware of and practice work discipline continuously in accordance with applicable laws and regulations.